PENGARUH FAKTOR FINANSIAL DAN NON FINANSIAL TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2013-2015) - Wanda Saputri, Gita Oktaviany; Achmad, Tarmizi (Diponegoro Journal of Accounting, 2017)
This research aims to examine the effect of financial factor and non-financial factor on earnings management. The financial factor of this study are explained using free cash flow and financial distress. The non-financial factor of this study is explained using employee diff. This study uses earnings management as dependent variable, independent variable used in this study are free cash flow, financial distress, and employee diff. Agency Theory and Attribution Theory are adopted to construct the hypotheses.This study use secondary data from annual reports and financial statements on  manufacturing companies listed on Indonesia Stock Exchange during 2013-2015. This sampling method used is purposive sampling. Total sample in this study are 230 data samples. This sutdy uses multiple regression analysis method to examine the effect of free cash flow, financial distress, and employee diff on earnings management.The result of this study indicate that free cash flow, financial distress, and employee diff had positive significant effect on earnings management.